Thoracic Trauma, Nonaortic Injuries - Jones, Kai A.; Sadri, Shirin; Ahmad, Noor; Weintraub, Joseph R.; Reis, Stephen P. (Seminars in Interventional Radiology, 2021)
Trauma is one of the leading causes of death worldwide. Approximately two-thirds of trauma patients have thoracic injuries. Nonvascular injury to the chest is most common; however, while vascular injuries to the chest make up a small minority of injuries in thoracic trauma, these injuries are most likely to require intervention by interventional radiology (IR). IR plays a vital role, with much to offer, in the evaluation and management of patients with both vascular and nonvascular thoracic trauma; in many cases, IR treatments obviate the need for these patients to go to the operating room. This article reviews the role of IR in the treatment of vascular an nonvascular traumatic thoracic injuries.
Keywords: trauma; hemorrhage; thoracic; pneumothorax; interventional radiology